Thailand Country Gender Assessment - World Bank (Washington, DC, 2022)
The purpose of this gender assessment is to support the development of Thailand’s Country Gender Action Plan (CGAP) (FY21–FY22) and to guide the World Bank Group’s efforts to address gender equality challenges relevant to meeting the priorities of the Country Partnership Framework (CPF) for Thailand. The diagnostic follows the framework of the 2012 World Development Report on Gender Equality and Development, with a focus on endowments, voice and agency, and economic opportunities. The first chapter is a country overview that outlines Thailand’s performance in global gender indexes and introduces institutional frameworks related to gender, including legislation, international obligations, and national policies and plans, and institutional mechanisms. The second chapter on human endowments details the progress in closing gender gaps in health and education outcomes, such as maternal mortality and fertility, as well as educational enrollment and attainment. The third chapter presents trends in women’s representation in senior levels of the public and private sectors, as well as the status of women’s political representation. The fourth chapter highlights emerging areas of concern, such as adolescent pregnancy, discrimination against lesbian, gay, bisexual, transgender, and intersex people (LGBTI) groups, and gender issues related to the conflict in Southern Thailand. Finally, the fifth chapter analyzes gender gaps in employment, wages, and information and communication technology (ICT) access and explores constraints on women’s work. It also looks at the impact of COVID-19 in exacerbating these gaps. The final chapter proposes recommendations for priorities that the World Bank Group could focus on moving forward.